The Travel to Search for the Great Learning in Ci Poetry of the Song Dynasty - Waranusast, Puriwan (Journal of Sinology (วารสารจีนวิทยา), 2010)
Chinese culture believes that travel is a process of learning. Travel also played an important role in Song society, due to its distinctive administrative organization. This kind of travel can be categorized into travel by duty, and travel by voluntary. Travel by duty shows two ideas which are the mandate of heaven (tian ming) and the policy of benevolence (ren zheng). Travel by voluntary can be divided into two groups, which are learning from the past and learning from the nature. All kinds of travel leads to self-cultivation which aims to serve state ideology. This conforms to the goal of the book Da Xue, which focuses on social organization.